Ecocriticism and the sense of place - Filipova, Lenka (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"The book is an investigation into the ways in which ideas of place are negotiated, contested and refigured in environmental writing at the turn of the twenty-first century. It focuses on the notion of place as a way of interrogating the socio-political and environmental pressures that have been seen as negatively affecting our environments since the advent of modernity, as well as the solutions that have been given as an antidote to those pressures. Examining a selection of literary representations of place from across the globe, the book illuminates the multilayered and polyvocal ways in which literary works render local and global ecological relations of places. In this way, it problematizes more traditional environmentalism and its somewhat essentialised idea of place by intersecting the largely Western discourse of environmental studies with postcolonial and Indigenous studies, thus considering the ways in which forms of emplacement can occur within displacement and dispossession, especially within societies that are dealing with the legacies of colonialism, neocolonial exploitation, or international pressure to conform. As such, the work foregrounds the singular processes in which different local/global communities recognise themselves in their diverse approaches to the environment, and gestures towards an environmental politics that is based on an epistemology of contact, connection and difference, and as one, moreover, that recognises its own epistemological limits. This book will appeal to researchers working in the fields of the environmental humanities, postcolonial studies, indigenous studies and comparative literature"--
Keywords: Place (Philosophy) in literature; Environmentalism in literature; Ecocriticism in literature; NATURE / Ecology; PHILOSOPHY / Ethics & Moral Philosophy